Variation in sperm morphology among Afrotropical sunbirds. (15th December 2015) - Omotoriogun, Taiwo C.; Laskemoen, Terje; Rowe, Melissah; Albrecht, Tomáš; Bowie, Rauri C. K.; Sedláček, Ondřej; Hořák, David; Ottosson, Ulf; Lifjeld, Jan T.
Abstract : Birds show considerable variation in sperm morphology. Closely related species and subspecies can show diagnostic differences in sperm size. There is also variation in sperm size among males within a population, and recent evidence from passerine birds suggests that the coefficient of inter‐male variation in sperm length is negatively associated with the level of sperm competition. Here we examined patterns of inter‐ and intra‐specific variation in sperm length in 12 species of sunbird (Nectariniidae) from Nigeria and Cameroon, a group for which such information is extremely limited. We found significant variation among species in sperm total length, with mean values ranging from 74 μm to 116 μm, placing these species within the short to medium sperm length range for passerine birds. Most of this variation was explained by the length of the midpiece, which contains the fused mitochondria and is an important structure for sperm energetics. Relative midpiece length was negatively correlated with the coefficient of inter‐male variation in sperm total length across species, suggesting that sperm competition may have selected for greater midpiece length in this group. We also mapped sperm lengths onto a time‐calibrated phylogeny and found support for a phylogenetic signal in all sperm length components, except head length. A test of various evolutionary or tree transformation models gave strongest support for the Brownian motion model for all sperm components, i.e. divergences were best predicted by the phylogenetic distance between lineages. The coefficients of inter‐male variation in sperm total length indicate that sperm competition is high but variable among sunbird species, as is the case with passerine birds at large.